2002
DOI: 10.1016/s0002-9440(10)64466-5
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Intestinal Inflammation in Mouse by Activation of Proteinase-Activated Receptor-2

Abstract: Proteinase-activated receptor (PAR)-2, a G-protein-coupled receptor for trypsin and mast cell tryptase, is highly expressed in the intestine. Luminal trypsin and tryptase are elevated in the colon of inflammatory bowel disease patients. We hypothesized that luminal proteinases activate PAR-2 and induce colonic inflammation. Mice received intracolonically PAR-2 agonists (trypsin, tryptase, and a selective PAR-2-activating peptide) or control drugs (boiled enzymes, inactive peptide) and inflammatory parameters w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
321
3
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 346 publications
(340 citation statements)
references
References 49 publications
15
321
3
1
Order By: Relevance
“…At different times after infection, mice were killed and colonic tissues were excised to assess macroscopic damage score using criteria de-scribed in ref. 5. Bowel wall thickness was measured with a caliper, and myeloperoxydase (MPO) activity, an index of granulocyte infiltration, was assayed as described (5).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…At different times after infection, mice were killed and colonic tissues were excised to assess macroscopic damage score using criteria de-scribed in ref. 5. Bowel wall thickness was measured with a caliper, and myeloperoxydase (MPO) activity, an index of granulocyte infiltration, was assayed as described (5).…”
Section: Methodsmentioning
confidence: 99%
“…PAR 2 , which can be activated by ''trypsin-like'' serine proteinases, plays both a proinflammatory and a protective role in inflammation (3). PAR 2 is highly expressed in the intestinal tract, where its activation induces acute inflammation of the mouse colon (4,5). Conversely, triggering of PAR 2 in the setting of 2,4,6-trinitrobenzene sulfonic acid (TNBS)-induced colitis exerts a pronounced antiinflammatory action (6).…”
mentioning
confidence: 99%
“…Although not as extensively studied as PAR-1, PAR-2 has also been shown to be involved in the pathogenesis of systemic inflammatory disorders (25)(26)(27)(28)(29). Nonetheless, PAR-2 is expressed on hippocampal, cortical, thalamic, hypothalamic, and striatal neurons in the brain and on dorsal root ganglia, myenteric, and submucosal neurons in the peripheral nervous system (7-9, 30, 31).…”
mentioning
confidence: 99%
“…Although studies have shown that PAR 2 -activating peptides caused relaxation of isolated airways and was protective against bronchoconstrictor challenge (Cocks et al 1999), other studies have shown that mice that lack functional PAR 2 showed extensive allergic response compared to wild-type mice, suggesting a prominent pro-inflammatory role for PAR 2 activation in airway diseases (Schmidlin et al 2002). Similar controversies also exist in the gut, where chronic and systemic treatment with PAR 2 agonist was protective against a chronic model of inflammatory bowel disease (Fiorucci et al 2001), while acute activation of PAR 2 in colonic tissues led to inflammation (Cenac et al 2002). Overall, PAR 2 is present in many cells involved in inflammation (endothelial cells, mast cells, neutrophils, eosinophils, epithelium, etc.…”
Section: Pars and Inflammationmentioning
confidence: 96%
“…A recent study by Ferrell et al (2003), has also demonstrated a prominent role for PAR 2 in an animal model of monoarthritis, PAR 2 -deficient mice did not developed signs of chronic inflammation. In the gut, acute activation of PAR 2 caused colitis characterized by gut wall edema, granulocyte recruitment, increased permeability and release of pro-inflammatory cytokines such as interleukin-1 and TNF-α (Cenac et al 2002). In the airways, the role of PAR 2 is controversial.…”
Section: Pars and Inflammationmentioning
confidence: 99%